Filsafat Nilai Moral dalam Pandangan Islam - Elvia Siskha Sari; Azmi Fitrisia; Ofianto Ofianto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
Philosophy of Moral Values in Islamic View. Moral values are important in the formation of the younger generation, both for the community. Currently, the moral damage of a child is influenced by family factors and the sosial environment. Moral education in the view of Islam is a science that teaches how to behave towards God's creatures, both dead and living. Morality is related to human behavior or actions as God's creatures. The Literature Review method or literature review with content analysis was chosen in the preparation of this research, sourced from journal articles, internet articles, books, and other related articles. The results of the study explain that the value of morality is something that can show a person regarding the right and wrong of an act he has done by humans, this has been explained in the Qur'an in Surah Al-Baqarah fathers 33 and 34, the principle of Sheikh Yusuf Al-Makassari namely "al-takhalluq bi akhlaq Allah" or having character with Allah's character which emphasizes ethics or morals is very important for a person's personality, as well as the thoughts of philosophers, namely Ibn Miskawaih, al-Farabi and al-Ghazali who explain morals based on religion will give happiness and individual safety in this world and the hereafter.